Understanding game play domain: An interpretive approach towards modelling educational games with multi-domain framework - Ahmad, M. (Institute of Electrical and Electronics Engineers Inc., 2015)
Game-based learning or educational games has a constantly positive impact on learners while offering a variety of knowledge presentations and providing multiple opportunities to be applied during learning process. The development of an effective educational game has been a challenge for game developers to understand the depth and relationships between game play (rules and regulations), game environment, learning theories, and subject-matter (subject content, learners, teachers) embedded in the educational game. Thus, the authors have proposed a multi-domain framework with extracted implicit vaguely supported relationships through a systematic literature review. These relationships are verified through qualitative interviews with eight (8) game-based learning experts to validate the relationships. This paper presents seven (7) implicit relationships based on game play domain and discusses their relevancy with game environment, learning theories, and subject-matter by applying interpretive hermeneutic approach of qualitative study. Consequently, this paper concludes seven (7) explicit relationships in perspective of game play for game developers to reflect on during the development process of educational games. Â© 2015 IEEE.